A Role for RE-1-Silencing Transcription Factor in Embryonic Stem Cells Cardiac Lineage Specification. (22nd February 2016) - Aksoy, Irene; Marcy, Guillaume; Chen, Jiaxuan; Divakar, Ushashree; Kumar, Vibhor; John-Sanchez, Daniel; Rahmani, Mehran; Buckley, Noel J.; Stanton, Lawrence W.
Abstract: During development, lineage specification is controlled by several signaling pathways involving various transcription factors (TFs). Here, we studied the RE-1-silencing transcription factor (REST) and identified an important role of this TF in cardiac differentiation. Using mouse embryonic stem cells (ESC) to model development, we found that REST knockout cells lost the ability to differentiate into the cardiac lineage. Detailed analysis of specific lineage markers expression showed selective downregulation of endoderm markers in REST-null cells, thus contributing to a loss of cardiogenic signals. REST regulates cardiac differentiation of ESCs by negatively regulating the Wnt/β-catenin signaling pathway and positively regulating the cardiogenic TF Gata4. We propose here a new role for REST in cell fate specification besides its well-known repressive role of neuronal differentiation.